Acid and alkali-resistant Dy4 coordination clusters: synthesis, structure and slow magnetic relaxation behaviors. Issue 11 (25th February 2021) - Yu, Shui; Hu, Huancheng; Chen, Yunkai; Chen, Zilu; Zhang, Zhanyun; Ding, Man-Man; Zhang, Yi-Quan; Liu, Dongcheng; Liang, Yuning; Liang, Fupei
Abstract : Two Dy4 coordination clusters with different skeletons exhibit slow magnetic relaxation behaviours and high stabilities in water and common organic solvents, as well as in acid and base solutions. Abstract : Two new [Dy4 ]-based coordination clusters [Dy4 (L 1 )2 (L 2 )4 (NO3 )2 (EtOH)4 ]·2MeOH (1 ) (H3 L 1 = 2-(β-naphthalideneamino)-2-(hydroxylmethyl)-1-propanol, HL 2 = 2-hydroxy-1-naphthaldehyde) and [Dy4 (μ4 -O)(HL 3 )4 (H2 L 3 )2 ]·3H2 O·EtOH·CH3 CN (2 ) (H3 L 3 = 3-(((2-hydroxynaphthaen-1-yl)methylene)amino)-propane-1, 2-diol) with planar and butterfly-like skeletons, respectively, were synthesized and characterized. This revealed that 1 is a field-induced single-molecule magnet with an effective barrier of U eff = 6.1 K under a dc field of 800 Oe and 2 shows slow magnetic relaxation behaviour with U eff = 2.6 K under zero dc field. The magnetic dilution method was applied to further investigate the magnetic relaxation behaviors of 1 and 2 ; as a result, slow magnetic relaxation behaviors of 1 and 2 were mostly attributed to the single Dy 3+ ions, which was also confirmed by the result of ab initio calculation. Interestingly, both of them possess excellent stability in water and common organic solvents, as well as in acid and base solutions with a wide pH range (2.5–14). Surprisingly, 2 is stable even in 18 M NaOH aqueous solutions, which is rarely reported in 0D coordination compounds and is a breakthrough for paramagnetic metal clusters in stability. It helps to develop chemically stable single-molecule magnets for their application in moisture and acidic/alkaline media.